Nanoformulated Recombinant Human Myelin Basic Protein and Rituximab Modulate Neuronal Perturbations in Experimental Autoimmune Encephalomyelitis in Mice - Saad, Muhammed A; Eissa, Noha M; Ahmed, Mohammed A; ElMeshad, Aliaa N; Laible, Götz; Attia, Ahmed S; Al-Ghobashy, Medhat A; Abdelsalam, Rania M; Al-Shorbagy, Muhammad Y (International journal of nanomedicine, 2022)
Introduction: Rituximab (RTX) and recombinant human myelin basic protein (rhMBP) were proven to be effective in ameliorating the symptoms of multiple sclerosis (MS). In this study, a nanoformulation containing rhMBP with RTX on its surface (Nano-rhMBPRTX) was prepared and investigated in comparison with other treatment groups to determine its potential neuroprotective effects on C57BL/6 mice after inducing experimental autoimmune encephalomyelitis (EAE). Methods: EAE was induced in the corresponding mice by injecting 100 [micro]L of an emulsion containing complete Freund's adjuvant (CFA) and myelin oligodendrocyte glycoprotein (MOG). The subjects were weighed, scored and subjected to behavioural tests. After reaching a clinical score of 3, various treatments were given to corresponding EAE-induced and non-induced groups including rhMBP, RTX, empty nanoparticle prepared by poly (lactide-co-glycolide) (PLGA) or the prepared nanoformulation (Nano-rhMBP-RTX). At the end of the study, biochemical parameters were also determined as interferon-[gamma] (IFN-[gamma]), myeloperoxidase (MPO), interleukin-10 (IL-10), interleukin-4 (IL-4), tumor necrosis factor alpha (TNF-[alpha]), nuclear factor kappa B (NF-kB), brain derived neurotrophic factor (BDNF), 2', 3' cyclic nucleotide 3' phosphodiesterase (CNP) and transforming growth factor beta (TGF-[beta]) along with some histopathological analyses. Results: The results of the Nano-rhMBP-RTX group showed promising outcomes in terms of reducing the clinical scores, improving the behavioural responses associated with improved histopathological findings. Elevation in the levels of IL-4, CNP and TGF-[beta] was also noticed along with marked decline in the levels of NF-kB and TNF-[alpha]. Conclusion: Nano-rhMBP-RTX treated group ameliorated the adverse effects induced in the EAE model. The effectiveness of this formulation was demonstrated by the normalization of EAE-induced behavioral changes and aberrant levels of specific biochemical markers as well as reduced damage of hippocampal tissues and retaining higher levels of myelination. Keywords: multiple sclerosis, experimental autoimmune encephalomyelitis, nanoparticle, rituximab, recombinant human myelin basic protein